Occurrence and ecological risk assessment of pharmaceutically active compounds in neotropical small basins, Brazil - Alessandro Minillo; William Deodato Isique; Claudia Andrea Lima Cardoso; Yzel Rondon Súarez (Acta Limnologica Brasiliensia, 2023)
Abstract: Aim The aim of our study was to evaluate the contamination levels of selected pharmaceutically active compounds (PAC) and their potential ecological threat to forested streams. Methods Samples of stream water were collected in the second largest city in Mato Grosso do Sul State in center-west of Brazil. Physicochemical parameters and concentrations of PAC were quantified in samples collected in six field campaigns. Ecological risk assessment (ERA) based on risk quotient (RQ) was performed based on the maximum measured concentration of PAC in water. Results Six pharmaceutical compounds were successfully quantified in the forested streams, namely caffeine, naproxen, diclofenac, estriol, estradiol and ethinylestradiol. From the point of view of ecological risk, ethinylestradiol (22,57), estradiol (1,46), diclofenac (16.99) and caffeine (5.30) can be considered as priorities PAC, as they present moderate to high risks to aquatic organisms and may also cause damage to the food chain. Conclusions This study provides valuable information to emphasize the importance of continuous monitoring of forested streams in the west central region of the country, as well as efforts to control the input of these micropollutants into watercourses.